Camel meat marketing and camel meat marketplace in the Algerian northern Sahara-case of the region of Souf- - Zakaria, Brahimi; Abdelhakim, Senoussi; Bernard, Faye (Emirates Journal of Food and Agriculture, 2020)
A field survey involving 62 camel butchers from Souf region the Algerian northern Sahara was implemented in order to establish a typology of camel butcher and collect data on camel meat marketing, the diversity in marketing practices and camel meat marketplace. The collected data allowed to identify 4 homogeneous groups of butchers well distinguished between them after cluster analysis. (specialized young camel butchers, non-specialized rural butchers, traditional non-specialized urban butchers, modern and old urban specialized butchers). The present study confirmed the predominance of beef meat compared to camel meat among consumers, camel meat consumption being less successful in its environment. In-depth studies on camel meat sector are mandatory to identify the bottlenecks invalidating the promotion of the camel meat consumption.